2012
DOI: 10.1104/pp.111.192328
|View full text |Cite
|
Sign up to set email alerts
|

Natural Hypolignification Is Associated with Extensive Oligolignol Accumulation in Flax Stems    

Abstract: Flax (Linum usitatissimum) stems contain cells showing contrasting cell wall structure: lignified in inner stem xylem tissue and hypolignified in outer stem bast fibers. We hypothesized that stem hypolignification should be associated with extensive phenolic accumulation and used metabolomics and transcriptomics to characterize these two tissues.1 H nuclear magnetic resonance clearly distinguished inner and outer stem tissues and identified different primary and secondary metabolites, including coniferin and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
95
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 84 publications
10
95
1
1
Order By: Relevance
“…An analogous situation to that in the spruce cell culture has been observed in flax (Linun usitatissimum) plants, whose outer stem tissues contain hypolignified bast fibers with increased levels of glycosylated oligolignols compared with the inner stem, which contains lignified xylem and a higher content of less polar oligolignols (Huis et al, 2012). The data obtained from flax mutants with lignified bast fibers suggest that, similar to that in the KI-treated spruce cell cultures ( Fig.…”
Section: Both Peroxidases and Laccases Are Likely To Have A Role In Psupporting
confidence: 54%
“…An analogous situation to that in the spruce cell culture has been observed in flax (Linun usitatissimum) plants, whose outer stem tissues contain hypolignified bast fibers with increased levels of glycosylated oligolignols compared with the inner stem, which contains lignified xylem and a higher content of less polar oligolignols (Huis et al, 2012). The data obtained from flax mutants with lignified bast fibers suggest that, similar to that in the KI-treated spruce cell cultures ( Fig.…”
Section: Both Peroxidases and Laccases Are Likely To Have A Role In Psupporting
confidence: 54%
“…The stems of these mutants also accumulated a series of 5-hydroxyguaiacyl-containing dilignol and trilignol hexosides (Vanholme et al, 2010). Recently, a wide range of oligolignol hexosides has been detected in wild-type Arabidopsis leaves , and some were also found in flax stems (Huis et al, 2012;Chantreau et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, oligolignol derivatives have been found in the stems of flax (Huis et al, 2012) and in the stems and rosette leaves of Arabidopsis (Vanholme et al, 2012b;Morreel et al, 2014). To …”
Section: The Core Structures Of the Vacuolar Oligolignols Are Consistmentioning
confidence: 99%
“…We have previously shown that lignification in flax appears to be partially modulated through transcriptional regulation of genes encoding lignin monomer biosynthesis and polymerization (Fenart et al, 2010;Huis et al, 2012). More recently, we generated and characterized a flax ethyl methanesulfonate (EMS) mutant population that has allowed us to obtain mutants for the CAD and C3H lignin genes through a TILLinG reverse genetics approach (Chantreau et al, 2013).…”
Section: Introductionmentioning
confidence: 99%